Digital Taaruf and the Mediation of Islamic Marriage Law: Maqasid al-Syarī'ah, Sadd al-Dhari'a, and Networked Religious Authority on Instagram - Khairul Fadli Rambe; Yusnita Eva; Mayang Belia Sameto; Nofan Alfandi (Balai Penelitian dan Pengembangan Agama Jakarta, 2026)
The shift of Islamic marriage practices to social media has given rise to a form of religiously mediated matchmaking whose legal status has yet to be adequately examined. This study analyses digital taaruf on the Instagram account (@taarufpadang) as a contemporary expression of Islamic family law: how do online intermediaries (wasith) facilitate sharia-compliant matchmaking whilst upholding its fiqh requirements? In response to public concerns that uncontrolled premarital interactions erode the moral boundaries of young Muslims in Padang, this platform positions itself as a trustworthy alternative. The research employs a juridical-empirical method with a qualitative case study—comprising interviews, observations and document analysis—interpreted through the framework of Indonesian Islamic family law, as well as the principles of maqāṣid al-syarī’ah, sadd al-dharī’ah and networked religious authorities. The findings suggest that these accounts’ structure interactions to prevent khalwat, whilst simultaneously shifting the authority to mediate from guardians and traditional kinship networks to digital administrators. Digital taaruf represents a tangible yet ambivalent reconfiguration of fiqh—extending the maqāṣid to the online sphere, yet raising new questions about authority, accountability and the limits of permissible digital interaction.